Phase II trial of capecitabine plus erlotinib versus capecitabine alone in patients with advanced colorectal cancer. (April 2017) - Vincent, Mark D; Breadner, Daniel; Soulieres, Denis; Kerr, Ian G; Sanatani, Michael; Kocha, Walter; Klimo, Peter; MacKenzie, Mary J; O'Connell, Anne; Whiston, Frances; Malpage, Anne S; Stitt, Larry; et al.
Aim & methods: Capecitabine monotherapy as palliation for advanced colorectal cancer (CRC) is generally well tolerated. Adding erlotinib, an EGFR-tyrosine kinase inhibitor, might improve efficacy versus capecitabine alone. 82 patients received capecitabine alone (Arm 1) or capecitabine with erlotinib (Arm 2).Results: Median time-to-progression (TTP) in Arm 1 was 7.9 months versus 9.2 in Arm 2. In KRAS -wild type (WT) patients TTP was 8.4 and 11.7 months in Arms 1 and 2, respectively. In KRAS -mutated patients TTP was 7.4 and 1.9 months in Arms 1 and 2, respectively (p = 0.023). Arm 2 KRAS -WT patients, left-sided primaries, had an overall survival of 16.0 versus 12.1 months in right-sided primaries.Conclusion: Adding erlotinib to capecitabine increased TTP by 3.2 months in KRAS -WT patients. This study suggests that erlotinib harms patients with KRAS -mutated advanced CRC while it may provide benefit to those with KRAS -WT CRC. Further study of EGFR-tyrosine kinase inhibitors in patients with left-sided KRAS -WT CRC is warranted.